2014
DOI: 10.1002/jtr.2011
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Synthesizing the Effects of Festival Quality, Emotion, Festival Image and Festival Satisfaction on Festival Loyalty: A Case Study of Macau Food Festival

Abstract: This study aims to examine the interrelationships among the festival quality dimensions, festival quality, emotion, festival image, festival satisfaction and festival loyalty. Analysis of data from 454 attendees in the 12 th Macau Food Festival indicates that the proposed model fits the data. The result of this study will assist festival management in developing and implementing market-orientated service strategies to increase quality and image, and enhance the emotion and satisfaction of attendees in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
118
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(151 citation statements)
references
References 144 publications
(273 reference statements)
21
118
1
2
Order By: Relevance
“…Wu et al [29] concluded that festival quality had the significant effect on visitor satisfaction and behavioral intentions. Wong et al [28] found that festival quality affected attendee satisfaction and revisiting intention. Thus, there appears to be recognition of a significant effect from quality to value, satisfaction and revisiting intention in the literature.…”
Section: Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…Wu et al [29] concluded that festival quality had the significant effect on visitor satisfaction and behavioral intentions. Wong et al [28] found that festival quality affected attendee satisfaction and revisiting intention. Thus, there appears to be recognition of a significant effect from quality to value, satisfaction and revisiting intention in the literature.…”
Section: Hypothesesmentioning
confidence: 99%
“…Castéran and Roederer, 2013 and Shen, [21]), festival quality (e.g. Wong et al, [28] and Wu et al, [29]), festival value (e.g. Lee et al, [15] and Yang et al, [30]), and satisfaction with festival (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies contend that the more positive image perceived by the customers, then the higher their intention to loyal. In accord to these studies, some studies in the area of tourism have identified the importance of event or festival image (Gibson, Qi, & Zhang, 2008;Kaplanidou & Vogt, 2007;Moon, Ko, Connaughton, & Lee, 2013;Wong, Wu, & Cheng, 2014). These studies indicate that individuals have intention to revisit an event or a festival when they perceive a positive image of the event or festival.…”
mentioning
confidence: 92%